2007
DOI: 10.1017/s1368980007258379
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the influence of eating location on the diets of Irish children

Abstract: Objectives: To examine the influence of eating location on the quality of the diets of Irish children and to compare intakes at home with intakes at other people's homes and intakes outside the home, and to compare intakes at various locations outside the home. Design: Food intake was measured using a 7-day weighed diary in 594 children from the Republic of Ireland (aged 5-12 years). Details of where the food was prepared or obtained were also recorded. Results: Eighty-nine per cent of all eating occasions occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 24 publications
2
49
0
1
Order By: Relevance
“…Indeed, eating out-of-home is associated with increased EI and fat intakes (18)(19)(20) , and is an independent risk factor for obesity (21)(22)(23) . This is of particular concern given the increased frequency of out-of-home eating over time.…”
mentioning
confidence: 99%
“…Indeed, eating out-of-home is associated with increased EI and fat intakes (18)(19)(20) , and is an independent risk factor for obesity (21)(22)(23) . This is of particular concern given the increased frequency of out-of-home eating over time.…”
mentioning
confidence: 99%
“…Determinants of eating behaviour and dietary intake in children have been extensively researched, with increasing understanding of influences such as the food environment, particularly at home, where children eat most often (1) . A wide range of home-related factors such as socio-economic status (SES), affordability, availability at home and accessibility (2)(3)(4)(5) , to parental factors such as parent's education, nutritional knowledge and parental intake (3,(5)(6)(7)(8)(9) and individual factors such as food preferences (7,8) , have all been shown to relate to diet quality in children.…”
mentioning
confidence: 99%
“…The influence of eating occasion on the diets of 5-12-year-old Irish children was examined (52) . Findings showed that food consumed from outside the home (e.g.…”
Section: Eating Locationmentioning
confidence: 99%
“…When compared with food consumed at home, food consumed from outside the home was found to be richer in fat (37 v. 33 %E) and less fibre-dense (10 v. 14 g/10 MJ). 'Red meats (beef, pork and lamb)' 'vegetables' and 'potatoes' were less likely to be consumed outside the home; whereas chips, meat products, pizza, confectionery and savoury snacks made the greatest contribution to foods consumed outside the home (52) . As acknowledged by the authors of this study (52) , it is difficult to make comparisons with other published data, primarily due to the different definitions used for 'food consumed outside the home'.…”
Section: Eating Locationmentioning
confidence: 99%